Implementation of Humanistic Learning Theory in Differentiated Learning - Barrotut Taqiyyah; Maghfiroh; Siti Ismiatus Su’adah; Diajeng Fatimatus Zahro; Alfan Nasrulloh; Nur Aini Dwi Arum; Siti Jamilatul Mutmainnah; Putri Isnawati; Ifa Risma; Jihan Herawati Ananda Putri; Henifa Izah; Muhammad Romadlon Habibullah (Journal of Practice Learning and Educational Development, 2025)
This study aims to examine how humanistic learning theory is implemented in differentiated learning at MI Azzahro Bojonegoro. Humanistic theory emphasizes the development of individual potential optimally through a personal, empathetic, and learner-centered approach. In the world of education, this approach is in line with the principle of differentiated learning that accommodates the different learning needs of students. By using descriptive qualitative methods, data were obtained through observation, interviews, and documentation. The results show that the application of a humanistic approach in differentiated learning can increase motivation, learning independence, and active participation of students in the learning process.